IPv6 Dynamic Address Tunnel Model Based on the Sliding Address Window - Zichuan Ma; Xiaohong Huang; Shen Yan; Pei Zhang (Dianxin kexue)
IPv6 network address hopping transmission technology can effectively prevent network attacks through traffic analysis.On the basis of the study of some related technologies，the concept of dynamic address chain was applied to the IPv6 network address hopping transmission technology and an IPv6 dynamic address tunnel model based on the sliding address window was proposed.The testing result and analysis show that the model can achieve the design goals.